Narcissistic Mothers in Modernist Literature : New Perspectives on Motherhood in the Works of D.H. Lawrence, James Joyce, Virginia Woolf, and Jean Rhys /: New Perspectives on Motherhood in the Works of D.H. Lawrence, James Joyce, Virginia Woolf, and Jean Rhys. ([2019]) - Rademacher, Marie Géraldine
No abstract available